PREVALENCE OF VARIOUS BETA LACTAMASES AMONG GRAM NEGATIVE BACILLI IN URINARY ISOLATES FROM PATIENTS IN A TERTIARY CARE HOSPITAL OF NORTHERN INDIA - RAMESHWARI, THAKUR; Atul, Kumar; Varsha, Chaudhary; Paramjit, Singh; Vk, Sharma; Agarwal, Nidhi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Urinary tract infections are considered among the most common infections, occurring either in the community or health-care setting. WeÂ are left with very few options for the treatment due to rapid development of antibiotic resistance among the organisms. To find out the prevalence ofÂ various types of Î²-lactamases among urinary isolates. Methods: Seven antibiotic discs (HiMedia) were placed in combinations and approximation in a particular sequence on a 90 mm diameter MuellerHinton agarÂ plate. Results: Out of a total 165 urinary isolates, 66 (40%) isolates were positive for extended spectrum Î²-lactamase (ESBL) production, AmpC Î²-lactamases (AmpC) activity was present in 31 (18.78%) isolates, co-production of both ESBL and AmpC was seen in 16 (9.69%) isolates, 3 (1.81%) isolates produced metallo Î²-lactamase (MBL), 2 (1.21%) isolates produced both MBL, and ESBL and 1 (0.60%) isolates were positive for inducible thirdÂ generation cephalosporin resistance. Conclusion: With the presence of such high prevalence of various Î²-lactamases in clinical isolates of gram-negative bacilli and also other types of antibiotic resistance, antibiotic policy should be made, and strict adherence should be followed. Keywords: Extended spectrum Î²-lactamase, AmpC Î²-lactamase, Metallo Î²-lactamase.